ANALISIS KUALITATIF KANDUNGAN BUNGA KENANGA (Cananga odorata) SECARA FITOKIMIA dengan MENGGUNAKAN PELARUT ETANOL - Putri Ade Rahma Yulis; aisyah meiysa putri; Anasthasia oca muham; silvia anggraini; siti maisarmah (Journal of Research and Education Chemistry, 2020)
Cananga (Cananga odorata) is a tree or shrub that can be used to produce essential oils. In this study a qualitative test was conducted to study the content of secondary metabolites in cananga flowers. Based on research results cananga flowers contain flavonoids, tannins, saponins and steroids, while anthraquinone and terpenoids are not needed. The existence of secondary metabolite content in this plant is intended to be used as a raw material needed because it has an active metabolite content that links this plant to have antioxidant and other antibacterial properties.